2018
DOI: 10.1038/s12276-017-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of phospholipase D in the lifespan of Caenorhabditis elegans

Abstract: We have previously shown that phospholipase D (PLD) downregulation accelerates cellular senescence, which is widely believed to play an important role in aging, by stimulating reactive oxygen species (ROS) accumulation in human cells. In this study, we examined the role of PLD in aging using the nematode Caenorhabditis elegans. The mRNA level of pld-1 was found to be inversely correlated with aging. RNAi-mediated knockdown of pld-1 expression in nematodes enhanced ROS and lipofuscin accumulation and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Bowhead whales and naked mole rats, two animals characterized by exceptional longevity, both exhibit unique phospholipid profiles (Borchman et al, ; Mitchell et al, ). The disruption of lipid hydrolases that regulate phospholipid metabolism has also been shown to decrease lifespan in worms (Park et al, ), flies (Kinghorn et al, ; Kunduri et al, ), and mice (Shinzawa et al, ). Conversely, treatment with phosphatidylcholine prolongs life in C. elegans under conditions of oxidative stress (Kim et al, ).…”
Section: Lipid‐related Aging Mechanismsmentioning
confidence: 99%
“…Bowhead whales and naked mole rats, two animals characterized by exceptional longevity, both exhibit unique phospholipid profiles (Borchman et al, ; Mitchell et al, ). The disruption of lipid hydrolases that regulate phospholipid metabolism has also been shown to decrease lifespan in worms (Park et al, ), flies (Kinghorn et al, ; Kunduri et al, ), and mice (Shinzawa et al, ). Conversely, treatment with phosphatidylcholine prolongs life in C. elegans under conditions of oxidative stress (Kim et al, ).…”
Section: Lipid‐related Aging Mechanismsmentioning
confidence: 99%
“…We also discovered that LINC00511 promotes the expression of the phospholipase D1 (PLD1) gene by increasing transcription process. PLD1 refers to phospholipase, which is enriched in neurons and pharyngeal muscles but is relatively absent in muscle and epithelial cells (Park et al, 2018). A previous study discussed that targeting PLD1 sensitizes cervical cancer by modulating LKB1 (Kang et al, 2016).…”
mentioning
confidence: 99%
“…Likewise, the phospholipase D gene pdl-1 was up-regulated by a 3.51 z-score, and it is also involved in the DAF-16 pathway. Park et al [ 40 ] observed that pdl-1 down-regulation causes ROS accumulation and decreases longevity. Thus, the increased expression of pdl-1 may indicate a damage response by Cichlidogyrus parasites.…”
Section: Discussionmentioning
confidence: 99%